SiGe-based re-engineering of electronic warfare subsystems - Lambrecht, Wynand; Sinha, S. 1981- (Signals and communication technology., 2016)
This book equips readers with a thorough understanding of the applicability of new-generation silicon-germanium (SiGe) electronic subsystems for the military purposes of electronic warfare and defensive countermeasures. The theoretical and technical background is extensively explained and all aspects of the integration of SiGe as an enabling technology for maritime, land, and airborne (including space) electronic warfare are addressed, including research, design, development, and implementation. The coverage is supported by mathematical derivations, informative illustrations, practical examples, and case studies. While SiGe technology provides speed, performance, and price advantages in many markets, sharing of information on its use in electronic warfare systems has to date been limited, especially in developing nations. This book will therefore be warmly welcomed as an engineering guideline that focuses especially on the speed and reliability of current-generation SiGe circuits and highlights emerging innovations that will help to ensure the sustainable long-term integration of SiGe into electronic warfare.